Daylight observation of 1P/Halley in 1222. (15th October 2018) - Choi, G.-E.; Lee, K.-W.; Mihn, B.-H.; Ahn, Y.S.
Abstract: It has been questioned whether comet 1P/Halley that appeared on 1222 September 9 was bright enough to be observed in daylight, as recorded in the Korean account. We investigate the light curve of 1P/Halley in the 1222 apparition considering brightness enhancement of the comet by forward-scattering, in order to verify the Korean account. We first analyze the Korean accounts of 1P/Halley observed in 1222, and of Venus and Jupiter appearing in daylight generally. We then determine the absolute magnitude ( m 0 ) and heliocentric power-law exponent ( n ) using observations made around the perihelion in 1986 and a formula considering brightness enhancement by forward-scattering. We apply the results to estimate the light curve of 1P/Halley in the 1222 event. According to the accounts, 1P/Halley underwent a sudden change in brightness and the conditions were good on the day the daylight observation was recorded. We also find that Jupiter could have been visible in daylight at about −2.1 mag. Regarding the light curve, we find that if the m 0 and n values are similar to those in a previous study, 1P/Halley could have been reached a maximum near mag −2 in 1222. In conclusion, there is a strong possibility that 1P/Halley was actually observed in daylight, inferring from observations and the predicted total visual magnitude at that time. Highlights: Comet Halley underwent a sudden change in brightness in its 1222 apparition, likely due to the forward-scattering. Estimated total visual magnitude of the comet was about −1.7 mag on 1222 September 9, considering the effect of the brightness enhancement by forward-scattering. Observation conditions in Korea on that day were good to the extent of which Venus was visible during the daylight. Reliability of the Korean account of the daylight observation of 1P/Halley in 1222 is high, inferring from the predicted total visual magnitude and historical records.